Subjective Experiences of Couples Intimacy: A Contemporary Social Dilemma [Experiencias Subjetivas de Intimidad en Pareja: Un Dilema Social Contemporáneo] - Barrientos-Delgado, J (Pontificia Universidad Catolica de Chile, 2017)
Recent cultural transformations have reshaped the experience of intimacy. This article presents and discusses the results of a qualitative study -conducted in Santiago, Chile- aimed at exploring, through life stories and focus groups, the meanings attributed to intimate relationships by 64 men and women (ages 38 to 45), contacted through snow ball sampling. Results show that people embody in their intimate relationships the social tensions ensuing from the coexistence of different social discourses regarding intimate experiences. While yearning for love and intimacy, they also feel threatened by the dependence, the loss of autonomy, and the giving up of individual projects that they associate with being in a couple relationship. It is argued that tackling these tensions requires a new conceptualization of intimacy, one that understands it as a discontinuous intersubjective process, marked by experiences of rupture and repair. In order to do this, the psychoanalytic concept of thirdness is used, which regards intimacy bonds as spaces of co-construction outside of the logic of complementarity.
Keywords: Biographic approach; Couple relationships; Cultural transformations; Intimacy; Thirdness